Human-Robot Interfaces in Exoskeletons for Gait Training after Stroke: State of the Art and Challenges - Claude Lagoda; Juan C. Moreno; Jose Luis Pons (Applied Bionics and Biomechanics, 2012)
Robotic rehabilitation of CVA (stroke) survivors is an emerging field. However, the development of effective gait rehabilitation robots used to treat stroke survivors is and remains a challenging task. This article discusses existing approaches and gives an overview of limitations with existing wearable robots. Challenges and potential solutions are being discussed in this article. Most difficulties lie in the implementation of physical and cognitive human robot interfaces. Many issues like actuation principles, control strategies, portability and wearing comfort, such as correct determination of user intention and effective guidance have to be tackled in future designs. Different solutions are being proposed. Clever anthropometric design and smart brain computer interfaces are key factors in effective exoskeleton design.